The Impact of the Participation Rate - Whatever it is -on University Enrolment - Darling, A. L. (Canadian Journal of Higher Education, 1980)
In the period from 1960 to 1976 the participation rate in university education increased dramatically and has since fallen. During this same period the size of the university age group doubled, so there was a period of great expansion in university enrolment. Popula- tion projections show a decline of the order of 20% in the size of the university age group between 1982 and 1996, and many believe that university enrolments must inevitably drop too, although the participation rate will be a major determinant of what happens. The factors which influence participation rates using the period 1960 to 1978, and the way in which participation rates are measured are examined. This is then applied to a discussion of the level of undergraduate enrolment in the period to 1996.